THE EFFECT OF ADDITIONAL SENTE FEED (Homalomena cordata scoot) ON WEIGHT GAIN AND SIZE BODY DIMENSIONS OF CROSSBREEDING PIG - I G. W., Yasa; Budaarsa, K.; Suranjaya, I G. (Jurnal Peternakan Tropika, 2019)
This study aims to determine the effect of the addition of sente (Homalomena cordata scoot) in the ration on weight gain and body dimensions of crossbred pigs. The study was carried out for 3 months at a pig breeding farm in Lumbung Kauh Village, Selemadeg Barat District, Tabanan Regency. The study design used a randomized block design (RBD) consisting of 4 treatments and 4 replications as a group. Four treatments were given: commercial ration (concentrate + rice bran) without sente (A) as a control, commercial ration (concentrate + rice bran) plus 2% sente (B), commercial ration (concentrate + rice bran) plus 4% sente (C), commercial rations (concentrate + rice bran) plus 6% sente (D). Variables observed included weight gain, increase in chest circumference, abdominal circumference, flank circumference, shoulder height, back height, hip height, body length, and real body length. The data obtained were analyzed with Variance, if there were significant differences (P <0.05), it would be continued with Duncans Multiple Range Test. The results showed that the feeding of forage in the form of sente to level 6% did not have a significant effect (P> 0.05) on weight gain and body dimensions, meaning that the provision of additional feed of sente in the diet of 6% level was still safe to be given to crossbred pigs.   Keywords: Sente plants, body dimensions of pigs